Inventory and Preservation Investment for Deteriorating Inventory System with Stock-dependent Demand and Partial Backlogged Shortages - Shah, Nita H.; Rabari, Kavita; Patel, Ekta (Yugoslav Journal of Operations Research, 2020)
The model deals with the stock-dependent demand as exhibiting a huge volume of commodities leads to draw more costumers and augment the trading of the goods. Objects like vegetables, fruits, medicines start getting deteriorate after some period of time that results in economical and financial loss. By taking care of this factor a constant deterioration rate is considered as controllable by the use of suitable preservation technologies. Preservation technology investments are made for a valuable business as it helps to decrease the rate of deterioration. This model allows shortages, and back-ordering is permissible to manage the loss that occurs due to perishable objects and shortages. The objective is to find the optimal cycle time, preservation technology cost, and positive inventory time. The paper also proves the convexity of the total cost through graphs with respect to decision variables. A sensitivity analysis of decision variables, with respect to different inventory parameters, is carried out to modify the model.